2013
DOI: 10.1007/978-1-4614-6846-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Cartesian Genetic Programming for Image Processing

Abstract: Combining domain knowledge about both imaging processing and machine learning techniques can expand the abilities of Genetic Programming when used for image processing. We successfully demonstrate our new approach on several different problem domains. We show that the approach is fast, scalable and robust. In addition, by virtue of using off-the-shelf image processing libraries we can generate human readable programs that incorporate sophisticated domain knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 21 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…Sample supervised segment generation can be seen as an explicit example of more general approaches found at the intersection of evolutionary computation and image analysis/computer vision [19]. A distinction can be made [14] based on the granularity of the search process-whether the search method is used to construct a segmentation algorithm/image processing method [20][21][22][23][24], common with cellular automata, mathematical morphology and genetic programming approaches, or either for tuning the free parameters of an algorithm [14,[25][26][27][28].…”
Section: Sample Supervised Segment Generationmentioning
confidence: 99%
“…Sample supervised segment generation can be seen as an explicit example of more general approaches found at the intersection of evolutionary computation and image analysis/computer vision [19]. A distinction can be made [14] based on the granularity of the search process-whether the search method is used to construct a segmentation algorithm/image processing method [20][21][22][23][24], common with cellular automata, mathematical morphology and genetic programming approaches, or either for tuning the free parameters of an algorithm [14,[25][26][27][28].…”
Section: Sample Supervised Segment Generationmentioning
confidence: 99%
“…This requires consideration of the elementary building blocks of ADTs, viz. products and coproducts 6 . The conversion of an ADT to and from this representation is described extensively by Hinze [24] and is beyond the scope of this article, but fortunately the Scala library Shapeless [25,26] provides complete support for this and a variety of other polytypic methods (e.g.…”
Section: Product and Coproduct Typesmentioning
confidence: 99%
“…Technically, this is often achieved by mapping the host language API of interest to individual functions in the GP instruction set. For instance, in order to manipulate programs which use the API of a computer vision library (e.g., OpenCV [3], as in the GP/GI work of [4,5,6]), one could provide adaptor code for each API call of interest. This task is nowadays greatly facilitated by availability of a rich choice of domain-agnostic software packages (ECJ [2], EpochX [7] and DEAP [8] to name a few), which offer a extensive support for the representations and operators of GP.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review of CGP can be found in [20]. In this work, we use a version called 'CGP for Image Processing' (CGP-IP) [21]. Previously CGP-IP has been applied to problems such as medical imaging, robot vision, terrain classification [22] and image filters.…”
Section: Learning Object Identification Using Cartesian Genetic Pmentioning
confidence: 99%
“…In this work, the function set comprises a large subset of the OpenCV image processing library. Over 60 functions are available, and a complete list can be found in [21]. This method enables inserting of domain knowledge into evolved programs, and also improves evolvability as operations that are useful can be used directly instead of re-evolving the same functionality.…”
Section: Learning Object Identification Using Cartesian Genetic Pmentioning
confidence: 99%